2010
DOI: 10.1111/j.1399-3062.2010.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of multiple antibiotic combinations against Nocardia: relationship with a short‐term treatment strategy in heart transplant recipients with pulmonary nocardiosis

Abstract: Initial PN treatment in HTx recipients can be successfully carried out with bactericidal combinations such as imipenem plus amikacin or moxifloxacin, administered IV for 3-4 weeks. Within 1 month, a significant clinical and radiological improvement may be observed. In our experience, a <3 month oral regimen with cotrimoxazole, moxifloxacin, or doxycycline may then be used. This may allow a reduction of side effects and treatment-related burden, without any recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 25 publications
4
38
0
3
Order By: Relevance
“…In 1982, Wallace et al reported 25 cases of pulmonary nocardiosis (in patients without SOT) and described a higher rate of relapse among patients receiving less than 4 months of treatment [14]. Almost 30 years later, in a retrospective description of 12 cases of nocardiosis after heart transplantation who received short-course (≤120 days) antibiotic treatment, Tripodi et al [15] reported that none of their patients who were treated with 3-4 weeks of intravenous bactericidal antibiotics followed by 1-3 months of oral antibiotic relapsed. Reducing antibiotic treatment duration could have potential benefits, such as cost savings and reduction in the risk of adverse events, especially among transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1982, Wallace et al reported 25 cases of pulmonary nocardiosis (in patients without SOT) and described a higher rate of relapse among patients receiving less than 4 months of treatment [14]. Almost 30 years later, in a retrospective description of 12 cases of nocardiosis after heart transplantation who received short-course (≤120 days) antibiotic treatment, Tripodi et al [15] reported that none of their patients who were treated with 3-4 weeks of intravenous bactericidal antibiotics followed by 1-3 months of oral antibiotic relapsed. Reducing antibiotic treatment duration could have potential benefits, such as cost savings and reduction in the risk of adverse events, especially among transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Total duration of antibiotic treatment was recorded, and a short-course was defined as ≤120 days [15].…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbapenem usually displays a low MIC, and meropenem exhibits the best cerebral diffusion among this class. Time-kill studies showed that imipenem-amikacin and imipenem-moxifloxacin combinations are bactericidal for most isolates, whereas linezolid and SXT exhibit mainly bacteriostatic activity (16). The recognized patient intolerance to SXT, and the limit of the initial identification to the genus level, did not allow us to make a decision for antibiotic treatment based on the in vitropredicted susceptibility.…”
mentioning
confidence: 99%
“…While there have been no randomized controlled trials to allow the recommendation of an optimal therapy for pulmonary nocardiosis, in general, the agents most commonly used include trimethoprim-sulfamethoxazole, amikacin, carbapenems, and thirdgeneration cephalosporins (5,13), which were used successfully in our patient.…”
mentioning
confidence: 99%